Recent progress in electrochemical performance of carbon-based anodes for potassium-ion batteries based on first principles calculations. (1st September 2021) - Yuan, Fei; Zhang, Wenxin; Zhang, Di; Wang, Qiujun; Li, Zhaojin; Li, Wen; Sun, Huilan; Wang, Bo; Wu, Yimin A
Abstract: Carbonaceous materials and the composite materials of transition metals compounds in carbon matrix were widely used as anode for potassium-ion batteries (PIBs). During the research of these anode materials, first-principles calculations based on adsorption energy, density of states (DOSs) as well as diffusion energy barriers was regarded as an effectively approach to investigate their potassium storage mechanism. The underlying reasons for the improvement of electrochemical performance could be well illustrated via the corresponding calculations. Moreover, first-principles calculations also played a vital role to predict the material properties of electrodes before conducting experimental analysis. Hence, this review is to analyze in-depth the effect mechanism of K-adsorption energy, DOSs as well as diffusion energy barrier and so on for electrochemical performance of carbon-based anode materials. We summarized the corresponding research progress, the challenges of first principles calculations in PIBs, and proposed the corresponding strategies along with future perspectives for further development of carbon-based anode materials. This work not only can provide theoretical guidance for the development of anode materials with excellent physical and chemical properties, but also have reference significance for other energy storage systems.